2011
DOI: 10.2741/3895
|View full text |Cite
|
Sign up to set email alerts
|

Sources of diversity in T cell epitope discovery

Abstract: CD8-positive T cells respond to small antigenic peptide fragments presented on class I major histocompatibility complexes (MHCs). Those specific T cell epitopes capable of precipitating a cellular immune response are either derived from (altered) self (i.e. they are autoimmune- or cancer-associated) or come from foreign sources (i.e. they are pathogen-associated). Identification of T cell epitopes provides elementary information that can be employed in technologies that monitor and predict the likely outcome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 112 publications
(141 reference statements)
1
15
0
Order By: Relevance
“…To date, however, few studies have addressed whether this also translates to an efficient prediction of relevant human CD8 + T cell determinants, in particular, for Asian populations. Our previous studies suggested that bioinformatics tools may be inefficient for the prediction of CD8 + T cell epitopes in the context of Asian populations (9). In this study, we further confirm our observations in two different experimental settings.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…To date, however, few studies have addressed whether this also translates to an efficient prediction of relevant human CD8 + T cell determinants, in particular, for Asian populations. Our previous studies suggested that bioinformatics tools may be inefficient for the prediction of CD8 + T cell epitopes in the context of Asian populations (9). In this study, we further confirm our observations in two different experimental settings.…”
Section: Discussionsupporting
confidence: 89%
“…The lack of sufficient experimental data for these populations needed to adequately train the predictive algorithms is likely to contribute to this scenario (9). However, we do not exclude the possibility that algorithms could accurately predict epitopes that may have been missed by experimental screens.…”
Section: Experimental Validation Of Predicted Cd8mentioning
confidence: 97%
See 1 more Smart Citation
“…Using the encoded bead sets, the binding properties of MHC molecules can be determined for individual epitopes by measuring the stability of the complex through subunit-specific antibody staining as demonstrated for MHC variants of both human and murine origin. The exact contribution of amino 4 The abbreviations used are: pMHC, peptide-MHC; ␤2m, ␤2-microglobulin; HLA, human leukocyte antigens; J, 3-amino-3-(2-nitro)phenyl-propanoic acid residue; MES, 4-morpholineethanesulfonic acid; PB, Pacific Blue; PE, phycoerythrin. …”
mentioning
confidence: 99%
“…Such efforts are confronted with both an overwhelming diversity of potentially immunogenic peptide sequences and the polymorphism of the MHC system whereby each allelic product has a distinct peptide-binding motif that dictates their interactions. This has led to the development of a myriad of assays to probe either the ability of peptide-MHC (pMHC) 4 molecules to stimulate a specific population of T cells or ascertain the specificity and affinity of the peptide for a particular MHC variant (1)(2)(3)(4). Cell-free biophysical methods that employ soluble complexes purified to homogeneity have the advantage of directly measuring the molecular interaction between the peptide and MHC without the confounding effects of simultaneous expression of multiple MHC variants in a cellular context.…”
mentioning
confidence: 99%